Prostitusi Terselubung Di Suak Indrapuri - Iksan Iksan; Triyanto Triyanto; Yeni Sri Lestari (Jurnal Community, 2021)
This study aims to find out how the emergence of hidden prostitution in Suak Indrapuri, and how the impact on the surrounding community. The research method used in this study is qualitative. Snowball sampling was used to determine informants. The results of the study indicate that the existence of this hidden prostitution place has its aims and objectives for the Suak Indrapuri if at first glance there is indeed no place for prostitution that stands above the law but in social reality, there are some people who take advantage of certain places in the Indrapuri Suak. to commit prostitution (Zina). Some people feel benefited and some feel disadvantaged. Those who benefit are those who have a place in any form and provide it to those who practice prostitution, while the disadvantaged are those who are not involved but live around the location of the area, namely the Suak Indrapuri community itself. Keywords : Social Facts, Society, Prostitution, Suak Indrapuri, Social Problems